Effect of plasma-core-induced self-guiding on phase matching of high-order harmonic generation in gases - Major Balázs; Kovács Katalin; Tosa Valer; Rudawski Piotr; L'Huillier Anne; Varjú Katalin (2019)
In this work, we numerically study a self-guiding process in which ionization plays a dominant role and analyze its effect on high-order harmonic generation (HHG) in gases. Although this type of self-guiding-termed "plasma-core-induced self-guiding" in previous works-limits the achievable cutoff by regulating the intensity of the laser beam, it provides favorable conditions for phase matching, which is indispensable for high-flux-gas highharmonic sources. To underline the role of self-guiding in efficient HHG, we investigate the time-dependent phase-matching conditions in the guided beam and show how the spatiotemporally constant fundamental intensity contributes to the constructive buildup of the harmonic field in a broad photon energy range up to the provided cutoff. (c) 2019 Optical Society of America